2010
DOI: 10.1038/jid.2009.376
|View full text |Cite
|
Sign up to set email alerts
|

3,3′,4,4′,5,5′-Hexahydroxystilbene Impairs Melanoma Progression in a Metastatic Mouse Model

Abstract: Stilbenes comprise a group of polyphenolic compounds, which exert inhibitory effects on various malignancies. The aim of this study was to evaluate the antitumor effects of a previously unreported stilbene derivative-3,3',4,4',5,5'-hexahydroxystilbene, termed M8-on human melanoma cells. Cell-cycle analysis of the metastatic melanoma cell line M24met showed that M8 treatment induces G(2)/M arrest accompanied with a dose- and time-dependent upregulation of p21 and downregulation of CDK-2 and leads to apoptosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 41 publications
2
46
0
Order By: Relevance
“…On the other hand, our results pointing on the pro-angiogenic effects of RVT analogues should be considered with caution by those who working on these compounds (e.g. 3,3′,4,4′,5,5′-HHS) uncritically suggest their usefulness in the anti-cancer therapy [42, 43, 59]. The threat associated with the use of these stilbenes is related to stimulation of angiogenesis, especially in tissues which are known to accumulate senescent cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our results pointing on the pro-angiogenic effects of RVT analogues should be considered with caution by those who working on these compounds (e.g. 3,3′,4,4′,5,5′-HHS) uncritically suggest their usefulness in the anti-cancer therapy [42, 43, 59]. The threat associated with the use of these stilbenes is related to stimulation of angiogenesis, especially in tissues which are known to accumulate senescent cells.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the proliferation assays performed on various types of breast cancer cells treated with M8 revealed that IC 50 values for this stilbene range from 90 to 127 μM [12]. In studies on melanoma cells, IC 50 was between 20 and 25 μM [15]. Similar tendency was reported in the case of apoptotic potency of M8 which achieved the values near to maximal (100%) at the doses from 12.5 to 100 μM [13].…”
Section: Discussionmentioning
confidence: 68%
“…These studies are based on a paradigm that an introduction of additional groups into the stilbene structure strengthens biological properties of RVT analogues [11]. Of these newly synthesized derivatives, high expectations are linked with 3,3′,4,4′,5,5′-hexahydroxy- trans -stilbene (M8) which has been found to inhibit growth and/or induce apoptosis in various malignancies, including breast and colon cancers [12,13], leukemia [14], melanoma [15], and glioma cells [16] (Figure 1). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, hexahydroxystilbene (M8) inhibited cell migration in matrigel assays. In addition, hexahydroxystilbene (M8) inhibited melanoma tumor growth and prevented metastasis of melanoma cells to distant lymph nodes in the SCID mouse model [177179]. Monohydroxylated resveratrol (also, piceatannol) possesses better anti-tumor activity than resveratrol itself and is a potent COX-2 inhibitor.…”
Section: Phytochemicals For the Prevention/treatment Of Melanomamentioning
confidence: 99%